2015
DOI: 10.1007/s10147-015-0898-0
|View full text |Cite|
|
Sign up to set email alerts
|

Sarcopenia, but not visceral fat amount, is a risk factor of postoperative complications after major hepatectomy

Abstract: Sarcopenia was a risk factor for postoperative complications after major hepatectomy, particularly in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Muscle atrophy has been reported to be a prognostic risk factor for survival of HCC patients treated with living donor liver transplantation, resection, and sorafenib, as well as LC patients classified as CP‐A or CP‐B . Furthermore, muscle function loss has been reported to have a close relationship with cognitive function .…”
Section: Discussionmentioning
confidence: 99%
“…Muscle atrophy has been reported to be a prognostic risk factor for survival of HCC patients treated with living donor liver transplantation, resection, and sorafenib, as well as LC patients classified as CP‐A or CP‐B . Furthermore, muscle function loss has been reported to have a close relationship with cognitive function .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CLD, sarcopenia, MVL, and muscle strength decline are not rare, even in an early stage . In addition, MVL has recently been reported as a prognostic factor for survival in HCC patients treated with liver transplantation, surgical resection, or sorafenib, although few reports have elucidated the relationship between muscle function and prognosis of HCC patients following surgical resection. Although the difference was not statistically significant, the rate of postoperative infection was higher in patients with MVL than in those without that in the present study (11.4% vs 2.9%, P = 0.056), and our results also showed that MVL is an independent risk factor for death in HCC patients treated with resection.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the second most common cause of cancer‐related death worldwide and often develops in patients with CLD. In patients with both liver cirrhosis and HCC, MVL has been reported to be an independent risk factor for death . However, there have been few investigations of the relationship of muscle function with prognosis of HCC patients treated with surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, sarcopenia reportedly occurs in 40–70% of patients with cirrhosis, which is a higher prevalence than among patients with inflammatory bowel disease (approximately 20%) . In Japan, sarcopenia incidence among patients with cirrhosis has been reported to range from 10% to 70% …”
Section: Epidemiology and Clinical Significance Of Sarcopenia In Livementioning
confidence: 99%